(untitled) (Research, Society and Development, 2022)
The consumption of alcoholic beverages is related as a cause of more than 200 types of diseases, mainly liver cirrhosis, cardiovascular diseases and several types of cancer. The light-moderate use of alcoholic beverages, unlike heavy consumption, does not have clear influencing factors for the main diseases mentioned. This article aimed to elucidate the relationship between uncontrolled consumption of alcoholic substances and memory loss, based on highly credible research. It was an integrative exploratory literature review based on the analysis of eleven selected articles, which addressed the consequences of alcohol consumption in sufficient quantities capable of promoting changes in the homeostasis of the central nervous system. Through this review of human neuropathology related to alcohol, it was possible to identify some main factors that justify the pathologies caused by the consumption of alcoholic beverages. The results showed that excessive alcohol consumption negatively affects verbal episodic memory processes, i.e. storage and recall, as well as monitoring of verbal learning tasks. In addition to memory loss, other pathologies stood out in all studies, including metabolic damage to the central nervous system, damage to the hippocampus and frontal cortex, loss of cognitive flexibility and accelerated aging. It is concluded that there is a negative relationship between excessive consumption of alcoholic substances and memory loss.